(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2010)
Key words: Tamsulosin; Terazosin; IPSS; Qmax; PVR DOI: 10.3329/jcmcta.v20i1.4933 Journal of Chittagong Medical College Teachers’ Association 2009: 20(1):34-40